A inserção do assistente social, técnico-administrativo nas instituições federais de ensino superior em Sergipe - Oliveira, Carolina Sampaio de Sá (2021)
The insertion of Social Work in education took place in the 1930s, with a notable expansion from the 1990s onwards. After 10 years, it was possible to recognize the organization and mobilization of the professional category with the Federal Council of Social Work. The expansion process provoked by the Support Program for Restructuring and Expansion Plans of Federal Universities (REUNI), as well as the creation of the Federal Institutes of Education, Science and Technology (IFET), contributed to the expansion of higher education and to the expansion of of the professional staff of Social Work within the scope of education, aiming at the professional exercise of other competences and attributions distinct from the teaching profession. Allied to these determinations, from Decree nº 7.234, of July 19, 2010, which established the National Student Assistance Program (PNAES), student assistance was outlined in another way, as well as the number of professionals linked to him. In this scenario, the object of this study is to apprehend the possibilities of insertion of social, technical-administrative workers, in other socio-occupational spaces, in addition to student and teaching assistance, in the Federal Institutions of Higher Education (IFES), in Sergipe, that is, at the Federal University of Sergipe (UFS) and at the Federal Institute of Education, Science and Technology of Sergipe (IFS). It is important to emphasize the importance of articulating teaching, research and extension in the IFES to fulfill the social function of these institutions. The general objective is to analyze the alternatives for the insertion of social workers, technical-administrative, in the Federal Institutions of Higher Education, in Sergipe, from 2008 to 2020. The specific objectives are: to rescue the historical trajectory of the professional exercise of the /a social worker, technicaladministrative of the Federal Institutions of Higher Education, in Sergipe; identify the institutional demands that require a Social Work professional in these Institutions; to analyze the repercussions of changes in the educational policy, in particular, the one directed to higher education, in the working conditions of the social worker in the socio-occupational spaces in the Federal Institutions of Higher Education in Sergipe. The methodological conception chosen to support the research was historical-dialectical materialism, as it is understood that from there it is possible to analyze social dynamics as a totality, making it possible to identify the elements that have an impact on Higher Education. The research is documental, but qualitative in nature, the empirical sources are constituted of institutional documents such as management reports, as well as documents produced by the Federal Council of Social Service. Among the main results, it was possible to identify that UFS had social workers since the 1970s in extension, people management and student assistance, but at IFS these professionals have always been linked to student assistance. In this sense, we recognize that the IFES present a tendency of reductionism in the conception of education to student assistance, since there were no investments to expand the framework in sociooccupational spaces other than this one.